Review of The linguistics of the Voynich manuscript by Claire Bowern and Luke Lindemann. Issue 5 (3rd September 2021) - Timm, Torsten; Schinner, Andreas
Abstract: We address severe deficiencies of a recent publication by Claire L. Bowern and Luke Lindemann on the linguistics of the Voynich Manuscript [ Annual Review of Linguistics 2021 (7): 285-308].